Penentuan Pemilihan Komputer Untuk game online Pada Jasa Penyedia Warnet dengan Metode Multi-Factor Evaluation Process - Sinaga, Waris Pardingatan; Windarto, Agus Perdana; Damanik, Irfan Sudahri (TIN: Terapan Informatika Nusantara, 2022)
This study aims to help internet cafe service providers in choosing gaming computers that are in accordance with the needs factor. The method used is the Decision Support System using the Multi-Factor Evaluation Process (MFEP). Data is obtained by observing and interviewing the services of internet cafe providers in pematangsiantar city. The criteria used are 7 criteria: Processor (X1), Motherboard (X2), RAM (X3), VGA card (X4), Storage (X5), Casing (X6), Power Supply (X7) and 5 alternatives: Asus (A1) , Acer (A2), Lenovo (A3), Dell (A4) and Toshiba (A5). The results of the study indicate that the Toshiba alternative (A5) is the first recommendation with a final value of 3.95. Alternative Asus (A1) becomes the second recommendation with the final value 3.75 and Lenovo (A3) being the third recommendation with the final value 3.4.